In Appreciative Remembrance of Surasak Charoenwong: Aesthetics from an Awareness of Connection - Suwan, Sudwadee; Taothong, Suchart; Somthai, Pitiwat (Journal of Fine and Applied Arts Khon Kaen University, 2022)
This piece of research came into being because of the shocking loss of an important figure in Thai academic and art world. The objective of In Appreciative Remembrance of Surasak Charoenwong: Aesthetics from an Awareness of Connection is to collect, study, and analyze the multifaceted works of Professor Surasak Charoenwong, encompassing 42 literary pieces as well as numerous sets of visual art that synthesize interpretations from written language into the language of art. This research integrates elements of knowledge from Professor Surasak’s works with Buddhist psychology and the researcher’s appreciative remembrance of the artist’s method for creating images using visual elements, communicating through visual work in order to convey an aesthetic through mixed-media art. The research study shows how forms and methods used in deconstructing the works of Professor Surasak grew out of the use of colors, forms, and shapes laid one atop the other in various contexts, combined with the relationship between him and the researcher. Complex images are created in response to a sense of blurring and fading, suggesting comparisons to symbolic forms in Buddhist literature, following a concept of overlapping time to bring about illusory dimensions. This communicates emotion in an abstract way in the series “Lines, Colors, Spaces in Memory” through comparison with the researcher’s conscious perceptions and modified memories, linked with installation art: a new form of meaning is created through overlapping of periods of remembrance of having had, having existed, and having belonged to Professor Surasak. The intent is to encourage an awakening of the viewer’s imagination by linking the relationship between him and the researcher. The resulting sensations harmonize with recognition of the forms of existence in principles of Oriental philosophy, even though these may be expressed in visual art styles of the West.